The Relationship Between Share Price Movement and Audit Adjustments - Šušak, Toni (Oeconomica Jadertina, 2026)
The purpose of this research was to examine the correlation between the fluctuations in share prices following the release of independent auditor reports for companies listed on the Zagreb Stock Exchange during the period from 2016 to 2018, and the audit adjustments made to the financial results in their unaudited financial statements. The research hypotheses were evaluated using the regression coefficients derived from panel regression models that were estimated with a random effects estimator. The results of the research indicated a statistically significant positive correlation between the relative change in share price after the disclosure of independent auditor reports and the absolute earnings audit adjustments. In addition, there was a statistically significant positive correlation between the relative change in share price after the disclosure of independent auditor reports and the absolute upward earnings audit adjustments. However, no statistical significance was found between the relative change in share price after the disclosure of independent auditor reports and the absolute downward earnings audit adjustments. The lack of a significant correlation between downward earnings audit adjustments and share prices post-disclosure of an independent auditor’s report has raised further questions, thereby creating a new direction for future research. The study’s limitations include a relatively small sample size and the possible presence of omitted variable bias.